2022
DOI: 10.1007/s11764-022-01233-9
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and preliminary efficacy of iConquerFear: a self-guided digital intervention for fear of cancer recurrence

Abstract: Purpose Approximately 50% of cancer survivors experience moderate-severe fear of cancer recurrence (FCR). Self-guided digital interventions have potential to address the high level of FCR-related unmet needs at scale, but existing digital interventions have demonstrated variable engagement and efficacy. This study aimed to evaluate the feasibility and preliminary efficacy of iConquerFear, a five-module self-guided digital FCR intervention. Methods Eligible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 68 publications
(89 reference statements)
0
7
0
Order By: Relevance
“…In our research, the traditional CBT study 32 56 recent studies suggest that older adults also may benefit from it. An overview 57 suggested that a combination of face-to-face and digital services could be valuable to the elderly.…”
Section: Yearmentioning
confidence: 80%
See 3 more Smart Citations
“…In our research, the traditional CBT study 32 56 recent studies suggest that older adults also may benefit from it. An overview 57 suggested that a combination of face-to-face and digital services could be valuable to the elderly.…”
Section: Yearmentioning
confidence: 80%
“…An overview 57 suggested that a combination of face‐to‐face and digital services could be valuable to the elderly. A recent study has shown that older adults participate more in digital interventions to reduce FCR 56 . These results suggest that older people's digital literacy may have improved over the past decade or so 56 .…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…Within the oncology‐focused trials, DTx were tailored to be centered on patient support in the cancer recovery process within breast cancer and generalized cancers (Figure 3b); these DTx focus on maintaining social networks for the patient during the treatment process in addition to addressing cancer‐related anxiety 74 and lifestyle tracking 75 . These approaches often address orthogonal psychiatric issues related to the cancer itself such as depression 76 .…”
Section: Digital Therapeutics In Active Clinical Trialsmentioning
confidence: 99%